EXPLORING THE ETHNOMATHEMATICS FRACTAL CONCEPTS TOWARDS MINANGKABAU “SONGKET” TEXTILES”: A CASE STUDY IN WEST SUMATRA - Anna Cesaria; Sefna Rismen; Mazlini Adnan; Rahmatul Hayati; Edwar Kemal; Eka Pasca Surya Bayu (Curricula: Journal of Teaching and Learning, 2025)
Mathematics is often perceived as an abstract, universal, and culture-free discipline, presented in formal symbols and rigid procedures that appear distant from learners’ everyday realities. This research investigated fractal concepts in ethnomathematics in relation to the Minangkabau songket textile. This research employed a qualitative case study design. Data were collected using a document checklist of the songket and a semi-structured interview. Data were analyzed using document analysis and thematic analysis. The research population was the Minangkabau songket textile, and the sampling method was purposive; three songket motifs from Pandai Sikek, West Sumatra, were selected. The results reveal repeated patterns of self-similarity, iteration, recursion, symmetry, and statistical variation, which are similar to the structures seen in nature. These patterns are not the result of formal mathematical calculation but arise from indigenous knowledge grounded in the Minangkabau philosophy alam takambang jadi guru, where nature serves as the primary source of learning. Beyond their aesthetic function, the fractal properties of songket motifs serve as visual metaphors for cultural continuity, social harmony, and the intergenerational transmission of values. This research is limited to songket produced by Pandai Sikek in West Sumatra. This study reinforces the notion that traditional cultural products are not only artistic expressions but also repositories of sophisticated mathematical knowledge.